POAC-BASED MANAGEMENT STRATEGIES FOR MEMORIZING THE QUR’AN IN THE DIGITAL ERA - Nihayatuzzain Nihayatuzzain; Na’imah Na’imah; Izzatun Illiyyin; Aning Puspita Ningrum; Rasi A’yun Andhini Jati (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2026)
The rapid development of digital technology presents both challenges and opportunities in the process of memorizing the Qur’an, especially for individuals outside formal educational institutions, such as students, workers, and homemakers. Although several studies have explored memorization methods and the use of digital learning tools, research that systematically analyzes the management of Qur’an memorization using a formal management framework—specifically POAC (Planning, Organizing, Actuating, Controlling)—remains limited. This study aims to examine how the POAC management principles can be applied in the practice of memorizing the Qur’an in the digital age. The approach used is descriptive qualitative, with data collected through in-depth interviews with nine informants divided into three groups (students, workers, and homemakers), participatory observation, and a systematic literature review. Data were analyzed using thematic coding and source triangulation. The results indicate that the integrated application of the POAC framework has been proven to enhance the effectiveness and sustainability of memorization. Digital technologies such as the Quran Mobasher app, Tarteel AI, and the digital Qur’an serve as flexible facilitators, particularly in the areas of review (murajaah) and self-assessment. This study contributes to the management of Islamic education by demonstrating that the POAC framework can be effectively operationalized to manage Quran memorization in non-formal and digital learning contexts, although memorization conducted under the supervision of an institutional system is considered more effective than independent memorization without a formal structure.